PENERAPAN MODEL PEMBELAJARAN LEARNING STATION UNTUK MENINGKATKAN MOTIVASI BELAJAR DALAM PEMBELAJARAN PJOK MATERI SENAM LANTAI PADA SEKOLAH DASAR - Rio Fahmi Praditya; Yusuf Hanafi; Anang Marzuqi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low learning motivation in Physical Education, Sports, and Health (PJOK) classes remains a challenge in many elementary schools, particularly regarding floor gymnastics. This study aimed to enhance student motivation through the implementation of the "Learning Station" model. It was conducted as a Classroom Action Research (CAR) study spanning two cycles. The subjects were 29 sixth-grade students at SD Laboratorium UM during the 2025/2026 academic year. Data were collected using learning motivation observation sheets. The findings revealed a significant increase in learning motivation: the average motivation level rose from 51.7% in the initial phase to 64.8% in Cycle I, reaching 88.3% in Cycle II. All motivation indicators surpassed the established success target of 80%. These findings demonstrate that the Learning Station model is effective in boosting learning motivation in PJOK for sixth-grade elementary students.